The complexities of perceived and empirical reality on environmental performance: Industrial case studies in China, Lithuania and Poland - Craig, John H. S.; Lemon, Mark (Journal of Environmental Engineering and Landscape Management, 2010)
The culture of a company is often cited as the basis for how well that company performs both economically and environmentally. This can also lead to the development and adoption of generic management approaches that fail to adequately acknowledge the existence of multiple cultures within the organization or the potential disjuncture between how performance is perceived by personnel and any attempts to measure that performance in an ‘objective’ manner. This failure to respond to the complexity of multiple cultures and perceived performance and the instigation of over‐arching management systems can discourage constructive dissent and hinder the related capacity for innovation and improvement. This paper draws upon research into the level of congruence between perceived and objective measures of environmental performance in thirteen factories from the heavy industrial sector in China and Eastern Europe. It presents findings that suggest managerial interactions, both laterally and vertically, are mediated by socio‐cultural networks within and between family, community and workplace, resulting in a high level of unbounded complexity that influences the alignment between perceived and objective environmental realities.Aplinkos apsaugos veiksmingumo suvokimo ir empirinės realybės neatitiktis: Kinijos, Lietuvos ir Lenkijos įmonių pavyzdžiaiSantrauka. Įmonės kultūra dažnai siejama su imonės ekonominiu ir aplinkosauginiu veiksmingumu. Tai veda prie bendrų valdymo principų plėtojimo ir taikymo, tačiau šie principai nepakankamai įvertina organizacijoje egzistuojančias daugialypes kultūras arba galimą atskirtį tarp darbuotojų suvokiamo aplinkosauginio veiksmingumo ir bandymu jį „objektyviai” išmatuoti. Straipsnyje pateiktas tyrimas susijęs su įsivaizduojamų ir objektyvių aplinkosauginio veiksmingumo priemonių palyginimu trylikoje Kinijos ir Rytu Europos sunkiosios pramonės įmonių. Rezultatai įrodė, kad ir horizontalusis, ir vertikalusis vadovavimo principas yra veikiami socialinių‐kultūrinių ryšiu šeimose, bendruomenėse ir darbo aplinkoje, todėl neišvengiamai lemia sudėtingumą lyginant suvokiamą ir objektyvią aplinkos apsaugos realybę.Reikšminiai žodžiai: sudetingumas, kultūra, realybė, kalba, hierarchija.Понимание природоохранной действенности и сложность эмпирической реальности на примере предприятий из Китая, Литвы и ПольшиРезюме. Культура предприятия зачастую оценивается на основании экономической и природоохранной действенности предприятия. Это способствует развитию и приспособлению общих принципов управления, однако эти принципы в недостаточной степени оценивают многогранную культуру, царящую в организации. Можно различить понимаемую работниками природоохранную действенность и попытки объективно ее измерить. Представленное в статье исследование направлено на сравнение своеобразно понимаемых и объективных природоохранных мер на тринадцати предприятиях тяжелой промышленности в Китае и Восточной Европе. Результаты показали, что как горизонтальный, так и вертикальный принципы руководства действенны в семьях, обществах и рабочей среде с социально-культурными связями, поэтому обусловлены сложностями, оказывающими воздействие на объективную природоохранную реальность.Ключевые слова: сложность, культура, реальность, язык, иерархия.First Published Online: 14 Oct 2010